A Study On Ultra Fine Grinding Of Silica And Talc In Opposed Fluidized Bed Jet Mill [TJ1345. S187 2008 f rb]. - Thilagan Palaniandy, Samayamutthirian (2008)
Fine grinding is normally carried out in energy intensive grinding mills such as jet mill. Besides size reduction, jet mill also induced mechanochemical effect on the ground product.